2015
DOI: 10.1214/15-aoas865
|View full text |Cite
|
Sign up to set email alerts
|

Identifying heterogeneous transgenerational DNA methylation sites via clustering in beta regression

Abstract: This paper explores the transgenerational DNA methylation pattern (DNA methylation transmitted from one generation to the next) via a clustering approach. Beta regression is employed to model the transmission pattern from parents to their offsprings at the population level. To facilitate this goal, an expectation maximization algorithm for parameter estimation along with a BIC criterion to determine the number of clusters is proposed. Applying our method to the DNA methylation data composed of 4063 CpG sites o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…When comparing the findings from the proposed method and the results of HAN (Han et al (2015)), patterns of clusters 4 and 5 are consistent with the patterns of clusters 6 and 4 in the Table 7 from Han's work, which indicates that transmission patterns of these two clusters are insensitive overall with respect to the use of blocks. More importantly, it is interesting to see that a much larger number of CpGs showing paternal-predominance in DNA methylation transmission are identified, using the proposed method, especially when we use approach two to determine dependent blocks.…”
Section: Real Data Analysissupporting
confidence: 78%
See 2 more Smart Citations
“…When comparing the findings from the proposed method and the results of HAN (Han et al (2015)), patterns of clusters 4 and 5 are consistent with the patterns of clusters 6 and 4 in the Table 7 from Han's work, which indicates that transmission patterns of these two clusters are insensitive overall with respect to the use of blocks. More importantly, it is interesting to see that a much larger number of CpGs showing paternal-predominance in DNA methylation transmission are identified, using the proposed method, especially when we use approach two to determine dependent blocks.…”
Section: Real Data Analysissupporting
confidence: 78%
“…We use results from block-determination approach two (the less restrictive approach) to illustrate the differences. In Table 8 from Han et al (2015), 53 CpGs were identified as paternal-predominated transmission sites. Our approach identified three clusters (clusters 1 to 3; Table 5) with in total 794 out of 4063 CpG sites (around 15 times as in Han's work) such that DNA methylation transmission at those CpGs was mainly from paternal transmission and each cluster showed different levels of dominance with cluster 1 demonstrating the strongest paternal predominance and cluster 3 the weakest.…”
Section: Real Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The linear mixed model is more flexible in adjusting for covariates, accounting different types of study designs, and explicity addressing environmental variation (123, 126). In addition to studying epigenetic inheritance at level of individual CpGs, transgenerational inheritance can also be evaluated for groups of CpGs that share similar pattern of DNAm transmission (127). This approach, which incorporates unsupervised cluster into beta regression, was recently developed by Han et al (127), and was able to identify sets of CpGs that have same/different inheritance patterns between mother-offspring and father-offspring.…”
Section: Epigenetic Transmission Across Generations In Allergic Diseasementioning
confidence: 99%
“…Among these 1% CpG sites, most (~98%) DNA-M transmission is either dominated by the mother or transmitted evenly from mother and father. 23 …”
Section: Isle Of Wight 3rd Generation Cohortmentioning
confidence: 99%